Afzelin inhibits migration of MDA-MB-231 cells by suppressing FAK expression and Rac1 activation - Eva Rachmi&, Basuki Bambang Purnomo, Agustina Tri Endharti&, Loeki Enggar Fitri& (Journal of Applied Pharmaceutical Science, 2020)
Triple-negative breast cancer (TNBC) has the worst prognosis and the highest rate of metastasis among other types of breast cancer. These characteristics are supported by the dysregulation of focal adhesion kinase (FAK) and Rac1 which are the key players of mesenchymal cell migration on TNBC. Afzelin is a secondary metabolite that is contained in a variety of plants. This study explored the anti-migration effect of afzelin and its interaction with FAK and Rac1 on the highly invasive TNBC cell line, MDA-MB-231. Cell viability was assessed by 3-(4,5-dimethyl 2-thiazolyl)-2,5- diphenyltetrazolium bromide assay, and cell migration was evaluated using in vitro scratch assay. Rac1 activation was analyzed using the colorimetric assay, while vinculin and actin filaments were stained through immunofluorescence. The quantity of total FAK and phosphorylated FAK tyr397 was detected by Western blotting. Afzelin decreased cell viability and inhibited two-dimensional cell migration in a dose-dependent manner. Under confocal laser scanning microscopy, vinculin localization at the cell edge demonstrated a reduction of focal adhesion formation by afzelin. Further exploration showed that afzelin decreased FAK expression but did not affect FAK phosphorylation at tyr397. In addition, afzelin decreased Rac1-GTPase activation, which is a downstream effector of FAK. Taken together, these results suggest that afzelin suppresses TNBC cell migration, through inhibition of FAK expression and Rac1-GTPase activation.
Keywords: Afzelin, TNBC, cell migration, FAK, Rac1.